Analysis of Determinant Factors Customer Loyalty Towards Brand in The Telecommunication Industry With The Digitalization Paradigm - Agustinus Suradi; Sri Purwati; Muhammad Zakaria; Rezky Nurbakti; Fahrina Mustafa (Jurnal Sistim Informasi dan Teknologi, 2024)
The goal of this research is to determine whether company parties have implemented engagement strategies in the current digital context. This research uses a qualitative marketing research approach. We used a digital platform for the initial data collection stage. The analysis then continued with the creation of a textual corpus. A deep understanding of consumer engagement with brands can help companies build stronger relationships with consumers, create greater value for brands, and maintain a competitive advantage in the marketplace. By paying attention to emotional, cognitive, and behavioral dimensions, companies can develop more holistic and effective strategies for managing consumer engagement and strengthening their brand positioning. Research results reveal that consumers actively seek knowledge and information to enhance their decision-making about brands and products. Mobile telecoms have well-implemented Customer Brand Engagement strategies, but they also need to have a proactive approach in dialogue with customers to maintain their engagement. This means that in addition to understanding and responding to consumer needs and desires, companies also need to be proactive in communicating with customers to strengthen their relationship and engagement with the brand. According to a careful analysis of the lexical units in cluster one, the majority come from Twitter. Cluster two highlights the comparisons that consumers make regarding the technical characteristics of products and services with those of various competitors. Meanwhile, cluster three shows that consumers are increasingly looking for personal services that can meet their needs. Cluster four warns management about loss phenomena that are specific to certain areas or regions. Finally, Cluster Five allows management to understand that consumers are currently less involved in innovative services such as payments via smartphone.